Period dividing opportunistic networks mobility model based on human realistic scenarios - Gang CHENG; Yun-yong ZHANG; Yong ZHANG; Mei SONG (Tongxin xuebao)
Existing mobility models are unable to effectively reflect the behavioral trait of nodes during movement, so the period dividing opportunistic network mobility model based on human realistic scenarios was proposed, by setting up a node daily mobility model and dividing node mobility submodels according to time segment. The features of node activities based on the realistic human scenario and the opportunistic network mobility model were analyzed, in-cluding the node average detention time, the number of nodes in a community during different time interval and the changing frequency of destinations etc. And a contrast has been made between the collected realistic mobility data and data from other mobility models in the way of simulation. The results of simulation show that with respect to node meeting time interval etc., the performances of the model are closer to the activity features in realistic scenarios than other node mobility models.